ANALISIS MULTIATRIBUT ATTITUDE MODEL SEBAGAI STRATEGI MENYIAPKAN INOVASI, COMMERCE DAN PENGELOLAAN KEUANGAN EKONOMI KREATIF INDUSTRI KULINER DI SURAKARTA - Remon Gunanta; Widiyaningsih, Vitalis Ari ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2023)
The city of Surakarta as a center for the creative economy has enormous cultural wealth and creative people. However, the challenge for the creative economy is that many creative economies are still on a micro scale, where understanding and experience in innovation, commerce and management are still low. The aim of this research is to determine the readiness of creative economy actors in the culinary sub-sector in the city of Surakarta in carrying out innovation, commerce and financial management. This research also produces strategic input to produce better performance. The type of research is descriptive research, while the research method used is the Multiattribute Attitude Model (MAM). The research results show that creative economy actors in the culinary sub-sector are very ready to carry out innovation, commerce and financial management. Meanwhile, SWOT analysis can provide strategic input for the development of innovation, commerce and financial reporting.